Projeto Principia - Robôs na Escola: aprendizagem, desenvolvimento e cidadania - Italiano, Vinicius de Príncipe (2021)
Due to their potential, digital information and communication technologies (ICT), in addition to offering entertainment content, guarantee students access to images, videos, research and information, which facilitate the understanding of specific content, contributing to their learning and knowledge. Educational Robotics has the potential to contribute so that teenagers can glimpse new horizons for the use of TDIC, engaging them in learning projects and academic insertion. The main objective of this research is to analyze elements present in the initial activities of the Principia Project: Robots at School, together with the 6th year of elementary school in a public school, in the second half of 2019, that correlate with student development. To meet this objective of this research, we count on the contributions of Vygotsky, Paulo Freire and authors focused on ICT studies and, specifically, on Robotics in Education. The methodology adopted is based on theoretical and methodological contributions from Qualitative Research, in which the researcher acted actively as a participant, taking as a basis for understanding the facts. To record the events, the techniques of unsystematic observation and the production of field diaries were used. As a result of the research, we were able to conclude the identification of five elements: Project construction; Unplugged programming; Establishing connections between different situations and areas of knowledge; Programming and control of robots and reframing instruments. Such elements contributed for students to explore new content, build new learning and use technologies more profitably to leverage their development.